Alveolar soft part sarcoma in childhood and adolescence: Report of three cases and review of literature - Zhang, Yudi; Wang, Ying; Wang, Hao; Wen, Chuan; Wu, Xiaochuan (Frontiers in Pediatrics, 2022)
Alveolar Soft Part Sarcoma (ASPS) is a rare soft tissue sarcoma, which is rarer in children and has its unique tumor characteristics. Herein we present the immunophenotype, treatment and prognosis of 3 children ASPS from The Second Xiangya Hospital of Central South University, and 51 children ASPS has been reported in the previous literature, along with a focused review of the clinical features, pathological features, differential diagnosis and treatment prognosis of ASPS in pediatric patients.